Investigation of enhancing EDM machining performance of INCONEL alloy using composite electrodes - Shabarinathan KT; Senthilkumar K; Kathiravan N; Udhayachandran RM (Materials Research Express)
In this research, an attempt was made to reinforce aluminium with graphite particles and use it as a tool material with the objective of combining the properties of aluminium and graphite. The micrograph confirms that the graphite particles were uniformly distributed over the aluminium matrix, density reduces and thermal conductivity increases with the addition of graphite particles. Material Removal Rate (MRR) peaks at 12 A current before declining due to plasma channel expansion, an optimal Ton of 8 μ s ws observed, with 4 μ s Toff yielding higher MRR. Copper electrodes excel due to thermal conductivity, while 5% graphite in aluminum boosts MRR to 31.89 mm ^3 min ^−1 , additional graphite decreases MRR. TWR rises with shorter Toff until 6 μ s, then decreases. Gap control impacts TWR, with lower spark gaps causing higher TWR due to intense material removal, and higher gaps leading to increased TWR due to incomplete flushing. Copper electrodes have the lowest TWR due to their high melting temperature. The addition of graphite in aluminum reduces TWR at low currents but is less effective at higher currents. Surface roughness (Ra) decreases with higher current, reaching a minimum of 7.02 μ m at 12 A. Optimal Ton is 8 μ s (7.56 μ m), while shorter Toff at 4 μ s and a 3 mm gap yield the best Ra of 7.36 μ m with A4 composite tool. Copper electrodes result in higher Ra at higher currents, while graphite in aluminum improves surface quality, especially at 5% content. Arcing, an undesirable electrical discharge phenomenon in EDM, adversely affects machining. Experiments revealed a strong correlation between high duty cycles, duty ratios, and arcing propensity, with composite tools being more susceptible due to their variable conductivity. In contrast, non-composite tools, exemplified by copper, withstand higher duty ratios without arcing.